Detection of Mycotoxins in Poultry Eggs - Abdul-Shaheed, Dalia A.; Abbas , Oday S.; Jameel, Yasser J. (International Journal of Poultry Science, 2019)
Background and objective: Safe food is imperative for food production worldwide. Poultry eggs are crucial in the safe food chain; thus, special attention is directed towards the possible contamination of food and feed with fungi and the risk of mycotoxin contamination. This study aimed to identify the presence of Fumonisin (FU) and Zearalenone (ZON) in 100 laying poultry eggs in Diyala province. Materials and Methods: This study was carried out using high-performance liquid chromatography (HPLC). A total of 100 egg samples were randomly collected from different poultry farms in Diyala province. Data were analyzed using ANOVA. Results: The results obtained from the analysis of mycotoxins FU and ZON in the poultry egg samples were 94 and 82%, respectively. Conclusion: These findings indicate that there may be a risk for animal exposure to mycotoxins through the consumption of mold-infected feeds, which may affect consumer health.